Remote consultations in paediatric urology–Not just for pandemics?. Issue 2 (April 2021) - Charnell, Aimee M.; Hoen, Lisette 't; Sforza, Simone; Spinoit, Anne-Françoise; Radford, Anna
Summary: Although some centres have successfully integrated remote clinics into their paediatric urological practice, for many, remote clinics have developed due to the COVID-19 pandemic. One UK-based institution has integrated remote clinics in their practice for over two years and has developed guidelines considering which conditions may be suitable for remote consultations. These guidelines have been appraised by the European Association of Urology Young Academic Urologists paediatric working group. Through practical experience and anticipated difficulties, we have discussed considerations that paediatric urology departments should ponder when integrating remote clinics into their practice as we move forward from the pandemic.